Modern seismic technologies for studying fractured carbonate reservoirs of oil and gas - Yu.K. Tyapkin; I.Yu. Khromova; N.Ya. Marmalevskyi; O.M. Tiapkina (Геофизический журнал, 2020)
This article is a review of modern seismic technologies used in the study of carbonate reservoirs of oil and gas. Special attention is paid to areas of high fracture density, since the overwhelming majority of producing wells are associated with them. After analyzing the spatial behavior of natural fractures in carbonate rocks, we consider direct fracture indicators. They exploit azimuthal anisotropy of the amplitudes and velocities of both pressure and shear waves that is caused by an idealized model of fracture sets. Such a model assumes the presence of a fairly wide zone of flat, parallel and equidistant open fractures. Then, indirect fracture indicators, which are less demanding on the regularity of fracture behavior in space, are briefly analyzed. These are seismic post-stack attributes, such as dip angle, image coherence, curvature and other characteristics of reflecting horizons, as well as increased values of inelastic (in particular, azimuth-dependent) absorption and scattering of seismic waves. More attention is paid to simultaneous inversion of pre-stack seismic data, which allows calculating the ratio of the velocities of pressure waves and shear waves. Judging by numerous literary sources, relatively low values of this parameter serve as an indicator of the presence of fractures in carbonate rocks. We show that a set of parallel macrofractures can significantly affect the seismic estimates of this parameter and in no way affect its estimates from well log data. The impact of this mechanism is shown on the data from an area in the southeastern part of the West Siberian platform. Finally, the technology of imaging subvertical fractured zones (fractured corridors) using migration of duplex waves is considered. This type of waves has advantages over conventional reflected waves when visualizing subvertical objects. The effectiveness of this technology is demonstrated on seismic data from two areas in the Timan-Pechora oil-and-gas province.